Cannabinoid-2 Receptor Activation Attenuates Sulfur Mustard Analog 2-Chloroethyl-Ethyl-Sulfide-Induced Acute Lung Injury in Mice - Gregory Nicholson; Nicholas Richards; Janette Lockett; My Boi Ly; Raj V. Nair; Woong-Ki Kim; K. Yaragudri Vinod; Nagaraja Nagre (Pharmaceuticals, 2025)
Background: Exposure to sulfur mustard (SM; 2,2′-dichlorodiethyl sulfide) causes toxicity in the human body, particularly the lungs. The molecular mechanisms of SM-induced lung damage are elusive, and no effective treatments exist. This study explores the anti-inflammatory potential of cannabinoid receptor 2 (CB2R) activation in mitigating acute lung injury (ALI) and inflammation induced by 2-chloroethyl ethyl sulfide (CEES), a structural analog of SM. Methods: C57BL/6J mice were exposed to CEES via intratracheal administration to model ALI. CB2R activation was achieved through the intraperitoneal administration of HU308, a selective synthetic agonist. ALI and inflammation were evaluated at 48 h post-exposure to CEES. Bronchoalveolar lavage fluid (BALF) was collected to measure total cells, protein, and cytokines. Lung injury, inflammatory signaling in alveolar macrophages (AMs), and matrix metalloproteinase-9 (MMP-9) activity were assessed via histological analysis, immunoblotting, and gelatin zymography, respectively. Results: CEES exposure led to an increase in immune cell infiltration, pro-inflammatory cytokines (IL-6 and TNF-α), and pro-MMP9 levels in the BALF, which were significantly decreased by HU308 treatment. The activation of CB2R attenuated CEES-induced NF-κB activation and reduced pro-inflammatory M1 markers (iNOS, and Cox-2) but did not alter the increase in the M2 marker arginase-1. CB2R activation mitigated CEES-induced oxidative stress, as evidenced by lower levels of heme oxygenase-1 (HO-1) and reactive oxygen species (ROS) in mouse AMs. Additionally, 4-hydroxynonenal (4-HNE) levels were reduced in the lungs of HU308-treated mice but were elevated after CEES exposure. Conclusions: These findings suggest that CB2R activation alleviates CEES-induced ALI and inflammation in mice, supporting its potential as a therapeutic approach for vesicant-induced pulmonary injury.